Light manipulation as a route to enhancement of antioxidant properties in red amaranth and red lettuce - Bucky, Annika; Pičmanová, Martina; Porley, Victoria; Pont, Simon; Austin, Ceri; Khan, Tanveer; McDougall, Gordon; Johnstone, Alexandra; Stewart, Derek (Frontiers in Nutrition, 2024)
With the growing global population and climate change, achieving food security is a pressing challenge. Vertical farming has the potential to support local food production and security. As a Total Controlled Environment Agriculture (TCEA) system, vertical farming employs LED lighting which offers opportunities to modulate light spectrum and intensity, and thus can be used to influence plant growth and phytochemical composition, including antioxidants beneficial for human health. In this study, we investigated the effect of four red-to-blue light ratios of LEDs (R:B 1, 2.5, 5 and 9) on the growth and antioxidant components in red amaranth microgreens and red lettuce. Plant growth, total phenols, betalains, anthocyanins, vitamin C and antioxidant capacity (ferric reducing antioxidant power assay) were evaluated. A higher proportion of red light resulted in biometric responses, i.e., stem elongation in red amaranth and longer leaves in red lettuce, while the increase in the blue light fraction led to the upregulation of antioxidative components, especially total phenols, betalains (in red amaranth) and anthocyanins (in red lettuce). The antioxidant capacity of both crops was strongly positively correlated with the levels of these phytochemicals. Optimizing the red-to-blue ratio in LED lighting could be effective in promoting antioxidant-rich crops with potential health benefits for consumers.